Innovación etnoeducativa en la primera infancia ecos de tambores - Fajardo Torres, Neiver (Universidad Santiago de Cali, 2020)
This article socializes a pedagogical proposal called "ETHNO-EDUCATIONAL INNOVATION IN EARLY CHILDHOOD; "ECHOES OF DRUMS", developed with kinder garden students in a public school in Villagorgona, Valle del Cauca. The program is born by the lack of recognition of the cultural identity of the context; which makes them invisible and ignores them as cultural and ancestral richness of the world in which they live. In this regard, and for the development of the pedagogical intervention proposal, experiences were integrated from the identification of their customs and traditions, which were approached from the experiences of each one and worked from the guiding activities, recognized as teaching strategies for achieving meaningful learning in early childhood children. This made it possible to contribute to the recognition and strengthening of cultural identity, rescuing the ancestral value and creating spaces for the integration of the community where the echo of its drums became the cosmovision of its ancestral memory.